A Case Report of Cardiac Amyloidosis Highlighting the Importance of Strain Analysis - Andres Cordova Sanchez; Ryan Murphy; Suman Rao; Fidel Martinez; Stephanie Bryant; Debanik Chaudhuri (Case Reports in Cardiology)
Cardiac involvement in light-chain (AL) amyloidosis has a high mortality. Once cardiac symptoms are present, it is important to make a diagnosis as there is an inverse relationship between mortality and time of diagnosis. Echocardiography is usually one of the first tests performed. But strain analysis, which can provide important clues, is not routinely performed. This is a case of AL amyloidosis presenting with heart failure in which echocardiographic strain analysis was vital for its diagnosis.